Development of some morphological categories in Kannada: a study of children 6-8 years age range - MG, Subramanyaiah (Journal of All India Institute of Speech and Hearing)
Morphological markers are used to indicate change in nulnber, gender and tense. There are a number of morphological rules using which the morphological markers are applied to the original form. There are some rules which can be applied to all the form of a particular grammatical category. But there are other rules which hold good for only certain forms. Children acquire these morphological rules during their language development and they learn to use these rules gradually.